Voltage and Reactive Power Control of Front-end Speed Controlled Wind Turbine via H∞ Strategy - Haiying Dong; Shuaibing Li; Lixin Cao; Hongwei Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
According to the characteristics like rapidity, time variability and the uncertainty of the input mechanical torque of the front-end speed control wind turbine (FSCWT) with directly grid-connected electrically excited synchronous generator (EESG), a double-loop H∞control approach was proposed. In which, a simpilified structure of brushless excitation system was used. For the inner loop, first H∞excitation controller was designed for realizing a fast excitation control; the second H∞power system stabilizer (PSS) was designed by solving the Riccati equation for the purpose of eliminating the oscillation and desynchronization of generator may caused by fast excitation and improving the system transient stability, which ensured the generator with stable operation in grid-connecting and effectively solved the contradiction between fast excitation and transient stability. Then the designed H∞controllers were applied to the voltage and reactive power control system (VRCS), which realized the output voltage and reactive power control requriements by tuning the weighting functions. Simulation results show that the double-loop H∞control approach was more effective than the single H∞excitation control in voltage and reactive power control of FSCWT. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.2423